Partisipasi Masyarakat Lokal Dalam Pengelolaan Desa Wisata Tenganan Pegringsingan Di Kabupaten Karangasem - Anggun Dewi Roshinta; I Wayan Mertha; Hartanti Woro Susianti (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2022)
Tourism is a sector that gives huge contributions specifically the income to the economy for the goverment and people who live in Bali. Far from the pandemic of Covid-19, the central and the local governments were carrying out developments in the tourism sector which were implemented in the form of tourism villages. The development of a tourism village must be balanced with community participation which will greatly affect the progress of the tourism village itself, because the community plays a significant role as the host and the manager of the tourism village. This research aims to analyze the local community’s participation and the factors that influence the local community’s participation in managing the Tourism Village of Tenganan Pegringsingan in Karangasem Regency. The technique of collecting data was obtained through observation, survey, interview, documentation, and literature study. The research instrument was carried out by distributing questionnaires consisting of 16 indicators that is includes 5 (five) variables in the forms of participation. The sampling technique used was purposive sampling. Moreover, the data was obtained used descriptive qualitative analysis. The research results showed that the participation of strength had the highest average score of 3,64 which belongs to the category (often), and wealth participation had the lowest average score 2,50 belonging to the category (ever). The participation of the local community’s in Tenganan Pegringsingan Village dominates the skills participation, however, was less enthusiastic in participating in ideas. Factors that influence the are dominated by people aged 26-35 with the male gender. For education, the people who dominated are the community at the high school level specifically by people who work as traders with an income level of Rp. 1.100.000 – Rp. 3.000.000. Moreover, it is dominated by people who have lived for 16-30 years.